CNC machine tool work offset error compensation method. (October 2015) - Gu, Jie; Agapiou, John S.; Kurgin, Sheri
Abstract: Machine tool accuracy and repeatability is one of the most important considerations for manufacturing parts with the required quality for consistent performance in their assemblies. One of the most challenging areas has been the ability to quickly identify and evaluate the quasi-static and dynamic machine errors and apply the corresponding error models to compensate. Because there are many challenges associated with some methods, including the cost in design, analysis and control of precision machine tools, the compensation method has been the most effective approach to control part quality. However, error compensation by measurement of geometric errors is greatly affected by the error modeling and error measurement methods, which could require significant machine downtime to implement. This paper presents the development of a global offset compensation method utilizing the measurements of the machined part(s). The global offset for a machine tool is estimated through a model while utilizing the computed deviation between the measured and nominal dimensions of the part. Furthermore, the paper presents several other compensation concepts supporting the global offset method. The strengths and limitations of all compensation methods are also discussed.